2021
DOI: 10.1039/d1gc02914b
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical oxidative radical cascade cyclization of olefinic amides and thiophenols towards the synthesis of sulfurated benzoxazines, oxazolines and iminoisobenzofurans

Abstract: The heterocycles containing N and O are important structures in pharmaceuticals, agrochemicals and functional molecules. The synthesis of these compounds usually needs complex substrates and harsh reaction conditions. Herein, we...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 61 publications
1
33
0
Order By: Relevance
“…Based on the above results (Scheme 6) and the previous reports, 11 we proposed the following plausible mechanism in Scheme 6. Firstly, diphenyl selenide was oxidized at the anode to form a radical cation intermediate A , which divided into phenyl-selenium radical B and phenyl-selenium cation C , respectively.…”
Section: Resultssupporting
confidence: 54%
See 1 more Smart Citation
“…Based on the above results (Scheme 6) and the previous reports, 11 we proposed the following plausible mechanism in Scheme 6. Firstly, diphenyl selenide was oxidized at the anode to form a radical cation intermediate A , which divided into phenyl-selenium radical B and phenyl-selenium cation C , respectively.…”
Section: Resultssupporting
confidence: 54%
“…10 In recent years, some breakthroughs have been achieved in electrochemical selenation. 11 In 2018, our group 11 a developed electrochemical aminoselenation and oxyselenation of styrenes with H 2 evolution. Soon after, Sun, 11 b Cao, 11 c Guo 11 d and others 11 e – o reported related works, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, no desired product was achieved under standard condition when protecting group changed to others, such as benzyl, phenyl, acetyl, benzoyl, benzyloxyformyl, tert ‐butoxyformyl and sulfonamido formyl (Table S2). Instead, the product ( 5 ) of oxygen cyclization was obtained in excellent yield in our modified reaction when increasing the amount of diphenyl diselenide to equivalent of substrate 5s , comparing with the previous reported reaction with moderate yield [19] . In addition, evaluation of catalysts was also explored by changing diphenyl diselenide to substituted diphenyl diselenides, diphenyl bisulfide and dibenzyl diselenide (Table S3).…”
Section: Introductionmentioning
confidence: 52%
“…Instead, the product ( 5) of oxygen cyclization was obtained in excellent yield in our modified reaction when increasing the amount of diphenyl diselenide to equivalent of substrate 5s, comparing with the previous reported reaction with moderate yield. [19] In addition, evaluation of catalysts was also explored by changing diphenyl diselenide to substituted diphenyl diselenides, diphenyl bisulfide and dibenzyl diselenide (Table S3). It was found that nonsubstituted diphenyl diselenide displayed a best result while phenyl substituted in para-position showed a positive effect than that in meta-or ortho-positions.…”
Section: Introductionmentioning
confidence: 99%
“…Electrosynthesis is a green and sustainable synthetic tool using inexpensive, renewable and inherently safe electrons as mass-free reagents for the redox reaction of substrate molecules. 6 The past decade has witnessed a rapid development in electrosynthesis, especially in the area of anodic oxidation transformations. 7 The cathodic reduction reaction commonly requires a divided cell, which limits its application.…”
mentioning
confidence: 99%